Disclosure of sustainability reports of financial performance of textile and garment manufacturing companies on the Indonesia stock exchange - Wahyuni, Nur; Kahfi, Zul; Karim, Abdul; Rahim, Syamsuri (International Journal of Management and Sustainability, 2025)
This study aims to analyze the relationship between sustainability report disclosure and financial performance in textile and garment manufacturing companies on the Indonesia Stock Exchange (IDX). A quantitative approach with multiple regression analysis techniques is used. The data used comes from the annual reports of textile and garment companies during 2018–2023. Sustainability report disclosure is measured using the Global Reporting Initiative (GRI) index while the dependent variable is financial performance measured through return on assets (ROA), return on equity (ROE), and net profit margin (NPM). The results of the study indicate that sustainability report disclosure has a positive and significant effect on the company's financial performance. Companies with higher levels of sustainability disclosure have better financial performance in terms of profitability and operational efficiency. This finding confirms that transparency in sustainability aspects improves the company's image and has an impact on investor confidence and the company's competitiveness in the capital market. This study provides implications for textile and garment manufacturing companies to improve the quality of sustainability report disclosure as part of a long-term business strategy. This study can be a consideration for regulators in developing policies that encourage sustainable business practices in Indonesia.